Comparison of Caudal Bupivacaine and Bupivacaine-tramadol Combination for Postoperative Analgesia in Children Undergoing Lower Abdominal Surgeries - Abdul Sattar Shamsuddin, Maqsood Ahmed Siddiqui, Anum Zeb, Abid Rafiq Chaudhry, Tayyab Ali, Mamoona Shaikh, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The aim of current study is to determine the effectiveness of caudal bupivacaine and bupivacaine-tramadol combination for postoperative analgesia in children undergoing lower abdominal surgeries. Study Design: Randomized Control trial Place and Duration: Department of Anesthesiology Surgical ICU & Pain Management Ghulam Muhammad Mahar Medical College, Sukkur and Lahore General Hospital, Lahore, during the period from March 2021 to August 2021. Methods: There were 110 children of both genders with ages 2-8 years undergoing lower abdominal surgery were included in this study. A detailed demographics of enrolled patients, including age, sex, and weight were computed after obtaining informed written consent from each individual. Patients were equally divided in two groups. Group I had 55 patients and received combination of tramadol (1 mg/kg) and bupivacaine (0.5 ml/kg of 0.25%) and group II received only bupivacaine 0.5 ml/kg of 0.25% after induction of anesthesia in caudal epidural space. Post-operatively pain score, requirement of rescue analgesia and sedation score was assessed and compared among both groups. SPSS 24.0 was used to analyze complete data. Results: There majority males 35 (63.6%) in group I and 32 (58.2%) in group II. In group I mean age of the patients was 5.9±4.61 years and in group II mean age were 4.8±9.44 years. Mean weight of the patients in group I was 17.6±4.52 kg and in group II mean weight was 19.5±7.34 kg. During the first 24 hours, we noticed a reduced pain score in the bupivacaine–tramadol group. When it comes to postoperative analgesia, the bupivacaine-tramadol group had much longer analgesia durations and a significantly lower need for rescue analgesia with p value <0.003. Postoperative frequency of adverse effects in group II was greater found in 4 (7.3%) cases as compared to group I in 1 (1.8%) patients. Conclusion: In children having abdominal surgery, we found that caudal tramadol with bupivacaine provided more extended and better quality postoperative analgesia than plain bupivacaine.